The convergence between the Post-Keneysian and the ecological economy: Critical assessment and remarks on green financing - Bispo Santos, Luiz Henrique; Caixeta Andrade, Daniel (Brazilian Keynesian Review, 2023)
There are recent attempts to bring ecological economics and post-Keynesian economics closer, whose synthesis efforts are taking place in a context of intertwining economic, social, political, and ecological crises. From this integration, a new discipline called post-Keynesian ecological macroeconomics has been consolidated. This article seeks to recover this synthesis effort by analyzing the hard cores of post-Keynesian and ecological economics. The article highlights the importance of the so-called green finance, a relatively new topic, especially among ecological economists. We argue that the approximation between ecological economics and post-Keynesian economics allows a better understanding and framing of green finance as an essential analytical category for an ecological transition. Lastly, despite the environmental warnings, we show that funding for environmentally degrading activities is still increasing.